The role of formative and summative assessment in improving learning quality and student learning outcomes - Mustamin, Riska (Journal of Strategy and Transformation in Educational Management, 2024)
Formative and summative assessment are two types of assessment that complement each other in improving the quality of teaching and student learning outcomes. Formative assessments are conducted continuously throughout the learning process to monitor student progress, provide feedback and identify learning difficulties. Summative assessment occurs at the end of the semester or unit of study to determine the student's final grade. This article examines the role of formative and summative assessments in educational settings and provides recommendations for their effective implementation. Literary research is used as a research method, collecting and analyzing sources related to the topic. The results showed that formative and summative assessments can improve learning quality and student learning outcomes when implemented with appropriate, valid, reliable, fair, transparent and competency-based principles. Recommendations are to align formative and summative assessments with learning objectives, curriculum, and strategies. Use different assessment methods and tools that match the characteristics of the student and the learning material, and provide constructive, timely and meaningful feedback to students.